Karakteristik penderita suspect demam berdarah dengue berdasarkan penurunan trombosit di Instalasi Rawat Inap Puskesmas Tegalalang I tahun 2014-1015 - Pande Komang Gede Bayu Wikrama; I Wayan Putu Sutirta Yasa (Intisari Sains Medis, 2019)
Introduction: Dengue hemorrhagic fever are found in sub-tropic area and tropical. In the last 50 years, the incident has increased 30 times in the world. World Health Organitation with more than 70 % of the population are at risk of dengueÂ  lives in Asia. In the year 2007, Indonesia is a country of dengue hemorrhagic fever cases in Southeast Asia. Tegalalang is one of the district in Gianyar, which was having an increase in dengue hemorrhagic fever cases. This study aims to determine the characteristics of patients with suspected dengue fever based on a decrease in platelets in Inpatient Unit/Installation of the Puskesmas (Public Health Centre) Tegalalang I in 2014-2015.Methods: Study design using cross sectional model with secondary data from Puskesmas (Public Health Centre) Tegalalang I started in January 2014 to June 2015. In the medical records of observable characteristics by sex, age, occupation, and decreased thrombocytes count began from the day third, fourth, and fifth of the fever.Results: From 92 samples, 62% of men and 38% of women. The most samples between 15-24 years old and students are the most. Average thrombocytes on patients who began to be hospitalized on third day of the fever is 142.76x103/ml. Average thrombocytes on patients who began to be hospitalized on four days of the fever is 123.22x103/ml and average thrombocytes on patients who began to be hospitalized on fifth day of the fever is 88.67x103/ml.Conclusion: It can be concluded that the number of thrombocytes decrease in patients with suspected dengue hemorrhagic fever can occurs on in the fever on day third, fourth and fifth.